2021
DOI: 10.3389/fonc.2021.643550
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic, Endonasal Transsphenoidal Surgery for Tumors of the Sellar and Suprasellar Region: A Monocentric Historical Cohort Study of 369 Patients

Abstract: BackgroundThe endoscopic endonasal transsphenoidal approach (EETA) is an established technique for the resection of a large variety of benign sellar and suprasellar lesions, mostly pituitary adenomas. It has clear advantages over the microscopic approach, like a superior close-up view of the relevant anatomy and the tumor-gland interface, an enlarged working angle, as well as an increased panoramic vision inside the surgical area. We have been performing the EETA for over a decade, and this study will focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Another important aspect to consider during pituitary surgery is complications. As previously reported ( 49 , 50 ), we observed a higher proportion of surgical complications as higher Knosp grade of the PA. It is known that PAs invading the cavernous sinus are particularly surgically challenging due to their close proximity to critical neurovascular structures and their deep intracranial location.…”
Section: Discussionsupporting
confidence: 90%
“…Another important aspect to consider during pituitary surgery is complications. As previously reported ( 49 , 50 ), we observed a higher proportion of surgical complications as higher Knosp grade of the PA. It is known that PAs invading the cavernous sinus are particularly surgically challenging due to their close proximity to critical neurovascular structures and their deep intracranial location.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the NP change after expansive sponge extraction could better predict p-CFL than the first-day NP. Previous studies considered post-operative NP as an epiphenomenon of intra-operative CSF leak which would correlate with a higher risk of p-CFL ( 31 , 32 ). Head NCCT examination was routinely performed on the first day after operation when the patient’s bilateral nasal cavity was filled with an expansive sponge, and they were in a continuous supine position.…”
Section: Discussionmentioning
confidence: 99%
“…The transsphenoidal approach is more appropriate for grade 1a PAs. However, we preferred EEA, owing to its advantages including wide-angle view and elimination of brain retraction (12,14,(29)(30)(31). Special attention should be given to protect the residual pituitary gland intraoperatively.…”
Section: Discussionmentioning
confidence: 99%